Capital at Work in Antwerp’s Golden Age - Soly, Hugo (Brepols, 2021)
Erasmus Schetz, Gaspar Ducci, and Gilbert van Schoonbeke. Contemporaries made it indisputably clear that these three moneymakers were exceptional, from different perspectives and for different reasons, but all commentators implicitly or explicitly referred to their unique economic achievements, and they were right to do so. The exceptional careers of the three protagonists shed light on the potential of the most dynamic economic centre of Europe - and the world - during early globalization. Precisely because their economic initiatives were far more ambitious than what other businessmen in Antwerp could or would consider or achieve, their careers are ideal vantage points for observing and analysing ‘capital at work’. They also provide an opportunity to examine how commercial capitalism changed and/or was transformed, and in what measure the three protagonists extended the frontiers of capitalism.